Detection of Campylobacter and Salmonella in ostrich - Yew, Ee Ling; Abdul Aziz, Saleha; Abu, Jalila (Veterinary Association Malaysia, 2012)
Three ostrich show farms were visited to detect the presence of Campylobacter and Salmonella in the birds. Cloacal and skin swabs were taken from 31 ostriches which were clinically healthy. Campylobacter was isolated from one (1.6%) cloacal swab and Salmonella from two (3.2%) samples, a skin and a cloacal swabs; all were from different birds. Although the detection of the organisms was low, it could pose public health risk partly because of contact with the birds and the organisms in the faeces may contaminate the environment and it could be that they may be present in other birds but were not shed at the time of sampling.